Kinoform syntesis as an improved method to form a concealed image in optical security devices - Braginets, E.V.; Girnyk, V.I.; Kostyukevych, S.A.; Kurashov, V.N.; Soroka, A.A.; Moskalenko, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
It is well known that one of the basic functions of security holograms is the maximal complication of their non-authorized reproduction, in other words – counterfeiting. To solve the problem, concealed images that can be observed only under special conditions are placed into a structure of the hologram. A popular way to place concealed image in Diffractive Optically Variable Image Device (DOVID) is integration into DOVID's structure of a Concealed Laser-Readable Image (CLRI). Traditionally CLRI is a 2D Computer-Generated Hologram (2D CGH), which is a digitized Interference Fringe Data (IFD) structure, computed under the scheme of Fourier-hologram synthesis. Such hologram provides inspection of the second level with portable laser reading devices. While it is being read, two (+/– 1 order of diffraction) identical images are formed. It is very interesting to achieve a CGH, which restores the image only in one diffractive order or two different images in +1 and –1 orders of diffraction.